2019
DOI: 10.13031/trans.13052
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Export from Agricultural Watersheds in the Piedmont and Coastal Plain, North Carolina

Abstract: Abstract. Nitrogen (N) and phosphorus (P) input and export rates were determined in six rural, predominantly agricultural watersheds located in the Piedmont and Coastal Plain regions of North Carolina. Water quality monitoring was conducted at the outlets for 2.3 to 8.0 years to determine the annual N and P export from each watershed. Total N and P input and export from five of the six watersheds were correlated, with only a no-till cropland watershed differing. The correlation showed that N and P exports incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Local experts listed conservation concerns in a 2020; USDA FSA 2021), with current conservation focused on pasture management, including exclusion fencing (ponds and streams), as well as stream crossings and filter strips. Exclusion fencing is the most currently accepted structural practice; research has shown nitrogen (N), phosphorus (P), and sediment reductions 20%, 47%, and 60%, respectively, when implemented in these watersheds (Line et al 2016(Line et al , 2019.…”
Section: Southernmentioning
confidence: 99%
See 1 more Smart Citation
“…Local experts listed conservation concerns in a 2020; USDA FSA 2021), with current conservation focused on pasture management, including exclusion fencing (ponds and streams), as well as stream crossings and filter strips. Exclusion fencing is the most currently accepted structural practice; research has shown nitrogen (N), phosphorus (P), and sediment reductions 20%, 47%, and 60%, respectively, when implemented in these watersheds (Line et al 2016(Line et al , 2019.…”
Section: Southernmentioning
confidence: 99%
“…In comparison, ACPF placed approximately three times the number of conservation practices than that of the local experts in each watershed respectively. The use of contour buffer strips as an in-field practice was the most identified conservation practice by ACPF and placed in 75% of cropped fields; this is not a common practice in North Carolina partially because conservation tillage has been widely and successfully adopted with concomitant low sediment and nutrient loading (Line et al 2016(Line et al , 2019Schomberg et al 2020), but also because of the small field size (<5 ha). Between 2005 and 2019, only two contour buffer strips were installed in North Carolina (USDA 2021).…”
Section: Central Feed Grains Regionmentioning
confidence: 99%